2017
DOI: 10.1111/ejn.13650
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of neuronal and glial STAT3 in the spinal cord of the SOD1G93A mouse model of amyotrophic lateral sclerosis

Abstract: Signal transducer and activator of transcription (STAT) proteins are activated by phosphorylation in the spinal cord of patients suffering from amyotrophic lateral sclerosis (ALS). The major scope of our study is a comprehensive histological characterization of the mechanisms underlying neuronal and glial STAT3 activation in the pathogenesis of ALS using SOD1 mice. We calculated the fold changes (FCs, ratios vs. appropriate controls) of the numerical densities of the following phosphorylated STAT3-positive (pS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 70 publications
2
15
0
Order By: Relevance
“…Loss of the PPIase activity of Ranbp2 in mice promotes a post-transcriptional decline of hnRNPA2B1 levels [239], whereas novel small molecules against the PPIase pocket of CY of Ranbp2 promote a decline of hnRNPA2B1 in HeLa cells [240]. Hence, Ranbp2 emerges as a therapeutic target to control the pathogenicity of mutations in hnRNPA2B1 and the neuroprotection potential of other substrates, such as Stat3, in ALS [240,332].…”
Section: Heterogeneous Nuclear Ribonucleoproteins (Hnrnps)-mutationsmentioning
confidence: 99%
“…Loss of the PPIase activity of Ranbp2 in mice promotes a post-transcriptional decline of hnRNPA2B1 levels [239], whereas novel small molecules against the PPIase pocket of CY of Ranbp2 promote a decline of hnRNPA2B1 in HeLa cells [240]. Hence, Ranbp2 emerges as a therapeutic target to control the pathogenicity of mutations in hnRNPA2B1 and the neuroprotection potential of other substrates, such as Stat3, in ALS [240,332].…”
Section: Heterogeneous Nuclear Ribonucleoproteins (Hnrnps)-mutationsmentioning
confidence: 99%
“…16 Existing evidence has showed that in microglia and macrophages, high expression of STAT3 inhibits the excessive activation of microglia. 17 Some studies have suggested that the secretion of inflammatory cytokines by the activated immune system is related to the occurrence of depression. 18 There is a certain relationship between the secretion of inflammatory cytokines by the activated immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the SOD1*G93A ALS mouse model on a C57Bl/6 genetic background was chosen [17,18,26,45]. These mice exhibit the first measurable deficits in motoric performance at age 8.5 weeks [41], which is by definition within the pre-symptomatic phase [46]. Using the SHIRPA test battery, we were able to confirm these early motor deficits of the mouse line in house ( Figure S3).…”
Section: Discussionmentioning
confidence: 92%
“…Due to this limitation only sufficiently large groups of female mice were available for this treatment study. Progenies were analysed for presence of the human SOD1 gene by quantitative PCR, as previously described [46]. Copy numbers of the transgene were checked by calculation of the delta cycle threshold (∆CT) = CT internal control − CT gene of interest .…”
Section: Animalsmentioning
confidence: 99%